High-performance vitrimeric benzoxazines for sustainable advanced materials: design, synthesis, and applications - Anagwu, Festus Ifeanyi; Thakur, Vijay Kumar; Skordos, Alexandros A. (Wiley, 2022)
Polybenzoxazines are high-performance materials capable of replacing conventional thermosets such as phenolics, epoxies, and bismaleimides in composites manufacturing due to their excellent thermomechanical and chemical behavior. Their versatility and compatibility with biobased precursors make them an attractive option as composite matrices. Like other thermosets, polybenzoxazines are not recyclable and cannot be reprocessed. Incorporating dynamic bonds in benzoxazine monomers can produce vitrimeric polybenzoxazines, which can potentially overcome this limitation and can be tuned to exhibit smart functionalities such as self-healing and shape memory. Dynamic bond exchange mechanisms for vitrimer development such as transesterification, imine bond, disulfide exchange, transamination, transcarbamoylation, transalkylation, olefin metathesis, transcarbonation, siloxane-silanol exchange, boronic ester, silyl ether exchange, and dioxaborolane metathesis are potentially applicable to benzoxazine chemistry, with disulfide bond and transesterification having successfully vitrimerized benzoxazines with topological transitions at −8.5 and 88 °C, respectively. Benzoxazine vitrimers featuring glass transitions of 193, 224, and 222–236 °C are now known. These place polybenzoxazines at the forefront of the development of reprocessable and recyclable thermosetting polymers and composite matrices.
Keywords: benzoxazine; bond exchange; mechanisms; sustainability; thermosets; vitrimers